Genealogy, psychology, and identity - Nicolson, Paula, author.
1 online resource
Keywords: "Fully revised and updated, Genealogy, Psychology and Therapy highlights the importance of genealogy in the development of identity, and the therapeutic potential of family history in cultivating well-being. The popularity of amateur genealogy and family history has soared in recent times. We will never know any of the people we discover from our histories in person, but for several reasons we recognize that their lives shaped ours. Key approaches to identity and relationships lend clues to our own lives but also to what psychosocial factors run across generations. Attachment and abandonment, trusting, being let down, becoming independent, migration, health and money, all resonate with the psychological experiences that define the outlooks, personalities and the ways that those who came before us related to others. This new edition builds on the original book, Genealogy, Psychology, and Identity, by highlighting the work of Erik Erikson along with studies of the quality of attachment, historical social conditions especially war, forced migration, health inequalities and financial uncertainty, to enable a more detailed understanding of trauma and its long shadow, and to focus on how genealogy informs our identities and emotional health status, exploring the transmission of trauma across generations. The intergenerational transmission of trauma is examined using analysis of real-life family examples, alongside an assessment of a narrative therapy approach to healing. The book expands on how psychological practices together with genealogical evidence may impart resilience and emotional repair, and develops the discussion of the psychological methods by which we interconnect in a reflective way with material from archival data-bases, family stories and photographs and other sources including DNA. Showing how people can connect with archival material, using documents and texts to expand their knowledge and understanding of the psychosocial experiences of their ancestors, this book will be of interest to those researching their own family tree, genealogists and counsellors, as well as students and researchers in social psychology and social history"--